Stereoscopic Cinema and the Origins of 3-D Film, 1838-1952 - Ray Zone (University Press of Kentucky, 2014)
I have spent most of my life as an inventor of stereoscopic moving image systems. Lately my work has taken me to the theatrical cinema, although it was more than twenty years ago that I made the basic invention that led to the latest renaissance in 3-D digital movies. I was aware of some of the history of the medium, and I knew something about the men who put their time and energy—and to tell the truth in many cases, their life's blood—into the invention of the cinema and stereoscopic displays. But Ray knows a lot more of the story. It is a history replete with many false starts and often of people working ceaselessly only to have their inventions die a stillbirth. It is a history that could not have made any sense in the moment and can be seen to have a form only with the passage of time and the boon of hindsight. Ray has presented the facts of the early days of the parallel development of cinema and stereoscopic display technology and to some extent left it to us to connect the dots. It is often difficult to say how one inventor influenced another. Were they aware of the work of their contemporaries? How many of the many inventions described in this book got built? And how many that got built actually worked? Ray has comments about this and relies wherever possible on eyewitness reports, but these are often inexpert and contradictory, which is what one would expect in historical research.